2018
DOI: 10.1039/c8cc08099b
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced desorption of trivalent chromium from adsorbents: one step closer to sustainability

Abstract: Trivalent chromium can be repelled from surface-bound merocyanine upon visible light irradiation, avoiding any chemical desorbent, and thus secondary contamination, to restore the adsorption capacity of the exhausted adsorbents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…[137] The residual Cr 3+ on the exhausted SP@Fe 3 O 4 and SP@SW upon exposure to visible-light was 0.49 mg g −1 (68% Cr 3+ desorption) and 0.61 g m −2 (30% Cr 3+ desorption), respectively. [137] Binding potential of SP@Fe 3 O 4 was tested for metal ions with different valence states. Results revealed that relatively larger amounts of trivalent metal ions were released from the SP@Fe 3 O 4 surface upon exposure to visible-light, indicating efficient light-driven adsorbent regeneration with moderately stable complex formation.…”
Section: Photo-regulated Adsorbentsmentioning
confidence: 90%
See 4 more Smart Citations
“…[137] The residual Cr 3+ on the exhausted SP@Fe 3 O 4 and SP@SW upon exposure to visible-light was 0.49 mg g −1 (68% Cr 3+ desorption) and 0.61 g m −2 (30% Cr 3+ desorption), respectively. [137] Binding potential of SP@Fe 3 O 4 was tested for metal ions with different valence states. Results revealed that relatively larger amounts of trivalent metal ions were released from the SP@Fe 3 O 4 surface upon exposure to visible-light, indicating efficient light-driven adsorbent regeneration with moderately stable complex formation.…”
Section: Photo-regulated Adsorbentsmentioning
confidence: 90%
“…During synthesis, the SP derivative was covalently immobilized onto solid spherical magnetite, Fe 3 O 4 , particles and the amine-functionalized planar silicon wafer (SW) surface by carbodiimide/N-hydroxysuccinimide mediated coupling to form SP@Fe 3 O 4 and SP@SW for aqueous Cr 3+ adsorption and desorption. [137] In the dark, the adsorption capacities of Cr 3+ (C o : 20 mg L -1 ) on SP@Fe 3 O 4 and SP@SW were 1.54 mg g −1 and 0.88 g m −2 , respectively. [137] The residual Cr 3+ on the exhausted SP@Fe 3 O 4 and SP@SW upon exposure to visible-light was 0.49 mg g −1 (68% Cr 3+ desorption) and 0.61 g m −2 (30% Cr 3+ desorption), respectively.…”
Section: Photo-regulated Adsorbentsmentioning
confidence: 95%
See 3 more Smart Citations